Spatial-temporal analysis of urban-rural differences in the development of elderly care institutions in China - Li, Xiang; Li, Chen; Huang, Yi (Frontiers in Public Health, 2022)
Due to the decline in physiological functions, the rate of illness has increased significantly, leading to a rise in demand for healthcare and elderly care. With the overlapping impact of an ageing population, advanced ageing, empty nesting families and the weakening of traditional elderly care functions, the issue of elderly care for the empty nesters, the elderly alone and the disabled has become more prominent and has become a focal point of concern for all sectors of society. As an important supplement to the elderly care service system, institutional care, together with home care, community care and rural care, are mutually complementary. The study establishes a panel database of urban and rural elderly-care institutions in 276 cities from 2010 to 2016 and uses comprehensive measurements to reveal the spatial-temporal changes of urban and rural elderly care institutions in China. The study concludes that: ①the overall scores of elderly care institutions in urban areas show a "double high" spatial pattern, with coastal areas being higher than inland areas and urban areas higher than rural areas. ②Among the top 20 elderly care institutions scores, most of them are located in municipalities directly under the central government, provincial capitals, sub-provincial cities and economically developed large cities on the eastern coast, while the overall score of elderly care institutions in rural areas does not clearly point to large cities. ③the cities with higher overall scores for elderly care institutions in urban areas or rural areas have a clear eastern coastal pointing, and the level of overall scores in the eastern region is generally higher than that in the northeast and central and western regions. ④the elderly care institutions in urban areas are developing rapidly in terms of both hardware facilities and software conditions, while the elderly care institutions in rural areas are generally on a declining trend in all aspects. ⑤ the global spatial autocorrelation analysis of urban and rural elderly-care institutions has the characteristics of agglomeration, and the local spatial autocorrelation analysis of high-high agglomeration is concentrated in the Beijing-Tianjin-Hebei city cluster, Shandong Peninsula city cluster and Yangtze River Delta city cluster.